The classification and management of root resorption: Klasifikasi dan perawatan dari resorpsi akar - Amaliah, Fitrah; Dwiandhany, Wahyuni Suci (Makassar Dental Journal PDGI Makassar, 2025)
Root resorption is a physiological and pathological process that leads to progressive tooth damage, particularly the loss of den-tine, root cementum, and ultimately tooth loss. Generally, the process of root resorption is classified into internal and external cate-gories, with several subclassifications. Treatment for internal and external root resorption may include preventive measures such as adequate endodontic treatment, as well as therapeutic interventions, for example, the use of intra-canal materials and antibio-tics, surgery, or extraction. This study compiles existing and up-to-date knowledge on root resorption classification to facilitate sim-ple diagnosis and explains root resorption treatment based on its subclassifications in the field of dental conservation. It is con-cluded that the accuracy and early diagnosis of root resorption classification are crucial for determining appropriate treatment.